Characteristic Sounds Facilitate Object Search in Real-Life Scenes - Kvasova, Daria; Garcia-Vernet, Laia; Soto-Faraco, Salvador (Frontiers in Psychology, 2019)
Real-world events do not only provide temporally and spatially correlated information across the senses, but also semantic correspondences about object identity. Prior research has shown that object sounds can enhance detection, identification, and search performance of semantically consistent visual targets. However, these effects are always demonstrated in simple and stereotyped displays that lack ecological validity. In order to address identity-based cross-modal relationships in real-world scenarios, we designed a visual search task using complex, dynamic scenes. Participants searched for objects in video clips recorded from real-life scenes. Auditory cues, embedded in the background sounds, could be target-consistent, distracter-consistent, neutral, or just absent. We found that, in these naturalistic scenes, characteristic sounds improve visual search for task-relevant objects but fail to increase the salience of irrelevant distracters. Our findings generalize previous results on object-based cross-modal interactions with simple stimuli and shed light upon how audio–visual semantically congruent relationships play out in real-life contexts.